Non‐target profiling of bitumen‐influenced waters for the identification of tracers unique to oil sands processed‐affected water (OSPW) in the Athabasca watershed of Alberta, Canada. (4th December 2020) - Milestone, Craig B.; Sun, Chenxing; Martin, Jonathan W.; Bickerton, Greg; Roy, James W.; Frank, Richard A.; Hewitt, L. Mark
Abstract : Rationale: The objective of this study was to identify unique chemical tracers of oil sands process‐affected water (OSPW) to enable definitive discrimination of tailings pond seepage from natural bitumen‐influenced waters from the Canadian Alberta McMurray formation. Methods: The approach involved comparing unknowns from an unprecedented sample set of OSPW ( n = 4) and OSPW‐affected groundwaters ( n = 15) with natural bitumen‐influenced groundwaters ( n = 20), using high‐performance liquid chromatography/electrospray ionisation high‐resolution mass spectrometry (HPLC/ESI‐HRMS) operated in both polarities. Results: Four unknown chemical entities were identified as potential tracers of OSPW seepage and subsequently subjected to structural elucidation. One potential tracer, tentatively identified as a thiophene‐containing carboxylic acid [C15 H23 O3 S] −, was only detected in OSPW and OSPW‐affected samples, thereby showing the greatest diagnostic potential. The remaining three unknowns, postulated to be two thiochroman isomers [C17 H25 O3 S] + and an ethyl‐naphthalene isomer [C16 H21 ] +, were detected in one and two background groundwaters, respectively. Conclusions: We advanced the state of knowledge for tracers of tailings seepage beyond heteroatomic classes, to identifying diagnostic substances, with structures postulated. Synthesis of the four proposed structures is recommended to enable structural confirmations. This research will guide and inform the Oil Sands Monitoring Program in its efforts to assess potential influences of oil sands development on the Athabasca River watershed.